Public Relations Strategy of Diskominfo Binjai City in Enhancing the Positive Image of the Binjai City Government - Sembiring, Muhammad Alfin Eraninka; Ritonga, Sakti (International Journal of Social Science and Humanity, 2024)
This article discusses the Public Relations (PR) strategies implemented by the Department of Communication and Informatics (Diskominfo) of Binjai City to enhance the positive image of the Binjai City Government. This study adopts a qualitative approach, analyzing primary data from interviews with the head of the news and audiovisual division and the IKP (Public Communication and Information) team members of Diskominfo Binjai, along with secondary data from related documents. The analysis reveals that Diskominfo Binjai has employed various PR strategies, including information campaigns, social media activities, public events, and collaboration with local mass media. It was also found that the use of information and communication technology (ICT) is an integral part of their PR strategy. This study highlights the importance of PR in building and maintaining a positive image of local government in the current digital era, particularly concerning sensitive issues.